Respirer l’urbain en asthmatique et/ou en allergique. Hospitalité des espaces publics urbains et airs anthropocènes - Anne Bossé; Théo Fort-Jacques; Magdalena Romay (VertigO)
How can the experience of public urban spaces be understood as an atmospheric experience that ties the human body with contemporary environmental transformations? This article presents the first results of a survey based on itineraries with asthmatics and/or people with allergies, i.e. people who are hypersensitive to breathing. It aims to clarify the ways in which inhabitants seize the conditions and materialities of the air in the Anthropocene era. This research is linked to an experimental cartographic work conceived as a possible critical tool of the mutations of contemporary public spaces.